Analisis kemampuan penalaran matematis dan self esteem peserta didik pada materi Program Linear - Fitri, Adhenia; Noer, Sri Hastuti (Media Pendidikan Matematika, 2022)
This study aims to determine the mathematical reasoning ability and self-esteem of high school students in class XI in the science program in learning mathematics for the subject matter of linear programming. The type of research used is descriptive qualitative. The sample in this study was 20 students who would be given a test in the form of a description of five questions and a self-esteem questionnaire totaling twenty-six statements. Analysis of research data was carried out by analyzing the results of students' answers according to indicators of mathematical reasoning abilities and the results of the self-esteem questionnaire given. The results of the analysis of students' answers obtained research results that (1) based on the results of the analysis of each indicator include: (a) Presenting mathematical statements in the form of pictures or writing, (b) Proposing allegations, (c) Carrying out mathematical manipulations, (d) Drawing conclusions, (e) Arranging evidence and providing reasons and solutions, and (f) Checking the validity of the arguments, the results are that students' mathematical reasoning abilities are categorized as very low; and (2) self-esteem analysis of students is categorized as good. Based on the analysis, it was concluded that the reasoning ability and self-esteem of the students of SMA Negeri 1 Talang Padang in class XI of the Linear Program material were categorized as good